2009
DOI: 10.1111/j.1439-0469.2008.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic morphology of the coral-associated genusGobiodon(Teleostei: Gobiidae) from the Red Sea

Abstract: Trophic morphology plays a major role in niche diversification among the highly diverse fish fauna of coral reefs. It gives insight into feeding types and is useful in taxonomy, as it can be used to differentiate between species and to estimate phylogenetic relationships. The gobiid genus Gobiodon comprises obligate coral dwelling species that are widespread on Red Sea and Indo-Pacific reefs. Yet very little is known about their ecology and behaviour of feeding. In this study, viscerocranial and oral jaw morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Supplementary video 3 shows the obligate coral dwelling fish Gobiodon histrio leaving the shelter of its coral colony to catch plankton from the water column. This rare event, which was captured by the direct-recording system during sunrise, has not been documented before and provides a potentially important insight as the feeding behavior of this genus is not totally clear [ 38 , 39 ].…”
Section: System Assessmentmentioning
confidence: 99%
“…Supplementary video 3 shows the obligate coral dwelling fish Gobiodon histrio leaving the shelter of its coral colony to catch plankton from the water column. This rare event, which was captured by the direct-recording system during sunrise, has not been documented before and provides a potentially important insight as the feeding behavior of this genus is not totally clear [ 38 , 39 ].…”
Section: System Assessmentmentioning
confidence: 99%
“…The gut contents of each species contained a variety of items suggesting a broad generalist diet (Table I). Diet is thought to vary between species of Gobiodon depending on the morphology of their feeding apparatus (Riedlecker & Herler, 2009). Many of the dietary items observed in this study were found, however, in all species and were similarly ranked in terms of percentage abundance.…”
Section: Identification and Per Cent Composition Of Dietary Items In mentioning
confidence: 99%
“…This study is the first quantitative assessment of Gobiodon diets and provides evidence that coral‐dwelling gobies ingest coral tissue. Coral‐feeding behaviour has been observed in Gobiodon citrinus (Riedlecker & Herler, 2009) and G. okinawae (P.L. Munday, pers.…”
Section: Identification and Per Cent Composition Of Dietary Items In mentioning
confidence: 99%
“…Symbiotic gobies have a similar relationship with Acropid corals. Several gobies consume coral tissue (5 of the 19 species of Gobiodon are corallivores), but no species feeds exclusively on coral (26, 27). Most Acroporid coral colonies host at least one pair of gobiids (17), these fish remain in the same coral colony for most of their adult life, and death of host corals is commonly correlated with goby population decline (17).…”
mentioning
confidence: 99%
“…Most Acroporid coral colonies host at least one pair of gobiids (17), these fish remain in the same coral colony for most of their adult life, and death of host corals is commonly correlated with goby population decline (17). Gobies consume coral tissue [they also consume copepods (26) and algae growing against the coral base (27)]. Thus, like ants on Acacia , they receive shelter and food from their host, which they protect from a damaging competitor.…”
mentioning
confidence: 99%